In vitro activity of antimicrobial combinations against multidrug-resistant Pseudomonas aeruginosa - Lima,Denissani Aparecida Ferrari dos Santos (2013)
Introduction Pseudomonas aeruginosa isolates related to nosocomial infections are often resistant to multiple antibacterial agents. In this study, antimicrobial combinations were evaluated to detect in vitro synergy against clinical isolates of P. aeruginosa. Methods Four clinical P. aeruginosa isolates were selected at random among other isolates from inpatients treated at the public University hospital in Ribeirão Preto, SP, Brazil. Two isolates were susceptible to imipenem (IPM-S) and several other antimicrobials, while the other two isolates were imipenem and multidrug resistant (IPM-R). The checkerboard method was used to assess the interactions between antimicrobials. Results Combinations of imipenem or other anti-Pseudomonas drugs with complementary antibiotics, such as aminoglycosides, fosfomycin and rifampin, reached synergy rates of 20.8%, 50%, 62.5% and 50% for the two IPM-S and two IPM-R Pseudomonas isolates, respectively. Imipenem, piperacillin-tazobactam and ceftazidime yielded a greater synergy rate than cefepime or ciprofloxacin. Synergist combinations were more commonly observed when the complementary drug was tobramycin (65%) or fosfomycin (57%). Conclusions Some antibacterial combinations led to significant reductions of the minimum inhibitory concentrations of both drugs, suggesting that they could be clinically applied to control infections caused by multidrug-resistant P. aeruginosa.